2015
DOI: 10.1016/j.cell.2015.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Co-transcriptional DNA and RNA Cleavage during Type III CRISPR-Cas Immunity

Abstract: SUMMARY Immune systems must recognize and destroy different pathogens that threat the host. CRISPR-Cas immune systems protect prokaryotes from viral and plasmid infection utilizing small CRISPR RNAs that are complementary to the invader's genome and specify the targets of RNA-guided Cas nucleases. Type III CRISPR-Cas immunity requires target transcription and whereas genetic studies demonstrated DNA targeting, in vitro data have shown crRNA-guided RNA cleavage. The molecular mechanism behind this disparate act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
522
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(550 citation statements)
references
References 41 publications
27
522
1
Order By: Relevance
“…No difference was observed (Fig. 3), in agreement with the current view that type IIIA and most likely also type IIIB complexes strictly require transcription of their DNA substrates (Samai et al, 2015).…”
Section: Activity Assaysupporting
confidence: 80%
See 2 more Smart Citations
“…No difference was observed (Fig. 3), in agreement with the current view that type IIIA and most likely also type IIIB complexes strictly require transcription of their DNA substrates (Samai et al, 2015).…”
Section: Activity Assaysupporting
confidence: 80%
“…The puzzle was solved by the observation that plasmid immunity of Sulfolobus islandicus REY15A (a host of two different Cmr complexes) required transcription (Deng et al, 2013). Subsequently, it was shown that the Csm complex from Staphylococcus epidermidis also harbored a strictly transcription dependent DNA endonuclease activity (Samai et al, 2015). As the DNA and RNA endonuclease active sites were distinct, their roles could be genetically separated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified Csm complexes from Streptococcus thermophilus and Thermus thermophilus cleave ssRNA in vitro by a mechanism similar to that of the Cmr complex (Staals et al 2014;Tamulaitis et al 2014). The S. epidermidis Csm complex has recently been shown to harbor two independent endonuclease activities (Samai et al 2015). The complex is capable of cleaving ssRNA targets complementary to the crRNA; additionally, the complex cleaves double-stranded target DNAs within the nontemplate strand in a transcription-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Type III systems lack Cas3, and the protein responsible for target cleavage is Cas10, which contains polymerase-cyclase and HD-nuclease domains that are both required for the target degradation (31,32).…”
mentioning
confidence: 99%